Book Review: Paterson, L. (2015) Social Radicalism and Liberal Education (Concept: The Journal of Contemporary Community Education Practice Theory, 2016)
This book will be useful to anyone interested in understanding the history of liberal education in general and, more specifically, for those interested in how liberal adult education was interpreted and developed by radical social and educational reformers in the first half of the twentieth century. Putting this history together is, in my opinion, a really helpful contribution that students, educators and academics will find particularly beneficial. The fact that the author is an exceptionally clear, concise and authoritative writer adds to its value. Because of my own interest in adult education, I will focus on this specific dimension rather than liberal education and schooling, which the book also addresses. Another justification for this is that, as Paterson points out, liberal education was more often discussed in the context of adult education than it was in schooling.